The octopuppy - McKenna, Martin, 1969- (New York : Scholastic Press, 2015)
Edgar wanted a pet dog, but what he got instead was a rather brilliant octopus named Jarvis.
"First published in Australia in 2013 by Omnibus Books, an imprint of Scholastic Australia."
Keywords: Octopuses -- Juvenile fiction; Pets -- Juvenile fiction; Octopuses -- Fiction; Pets -- Fiction